2017
DOI: 10.1186/s40348-016-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and adaptation of the airway microbiota in the early life of cystic fibrosis patients

Abstract: Cystic fibrosis (CF) is a genetic disease in which bacterial infections of the airways play a major role in the long-term clinical outcome. In recent years, a number of next-generation sequencing (NGS)-based studies aimed at deciphering the structure and composition of the airways’ microbiota. It was shown that the nasal cavity of CF patients displays dysbiosis early in life indicating a failure in the first establishment of a healthy microbiota. In contrast, within the conducting and lower airways, the establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…Niche-microbe interaction models have been developed to better interpret the dynamics, composition and role of lung microbial communities 4,7,31,[48][49][50] . These models were focused on bacterial communities and suggested that relative abundances of bacteria were not driven by a neutral model of dispersion in CF 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Niche-microbe interaction models have been developed to better interpret the dynamics, composition and role of lung microbial communities 4,7,31,[48][49][50] . These models were focused on bacterial communities and suggested that relative abundances of bacteria were not driven by a neutral model of dispersion in CF 50 .…”
Section: Discussionmentioning
confidence: 99%
“…It could be hypothesized that the lower biomass in CF children compared to asthmatic and healthy children facilitates the colonization in the throat by additional pathogens as it decreases the competition pressure and colonization resistance by protective commensals represented by Prevotella , Neisseria , Streptococcus , and Veillonella . This theory is supported by the fact that in CF patients, the latter specific genera are decreasing in the lower airways after colonization by typical pathogens like Pseudomonas aeruginosa [ 8 , 29 ]. The commensal and protective role of core throat bacteria found here and also in healthy subjects is still not elucidated; especially, the specific role of anaerobes in the lower airways remains controversial [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normal gut microbiome inhibits systemic IgE responses through signals directed to toll‐like receptors of innate immune cells including mast cells and basophils, while the production of short‐chain fatty acids modulates dendritic cell responses . In patients with CF, deteriorating lung function is associated with decreased phylogenetic variety of the bacterial airway microbiome and enrichment in pulmonary pathogenic genera such as Staphylococcus aureus, Pseudomonas aeruginosa, Haemophilus influenza , and Burkholderia cepacia . The proportion of saprophytic fungal species, which is <0.1% under normal conditions, is increased in CF patients’ mycobiome and following antibiotic regimens .…”
Section: Aspergillus Fumigatus and Its Interaction With The Human Hostmentioning
confidence: 99%
“…However, the first two stages lack consensus definitions. The growth of A. fumigatus in the airways, also termed “carriage” or “colonization,” may be evidenced by culture‐based methods, galactomannan detection in bronchoalveolar lavage liquid, PCR assays, and more recently new‐generation sequencing methods and antigenemia measures . The detection of “precipitins,” which comprise mainly but not exclusively IgG, or anti‐ A. fumigatus ‐specific IgG, is sometimes considered as indicative of A. fumigatus carriage, but most teams distinguish genuine A. fumigatus colonization from anti‐ A. fumigatus IgG detection.…”
Section: Aspergillus Fumigatus and Its Interaction With The Human Hostmentioning
confidence: 99%